The ways of solving the problem of Ukraine's economy de-shadowing - Golovash, B.; Ivantsov, D.; Golovash, L. (Ways to Improve Construction Efficiency, 2020)
Shadow economy is very common in the modern economy and inherent in any state, regardless of its level of socio-economic development. The underground economy refers to economic transactions that are deemed illegal, either because the goods or services traded are unlawful in nature, or because transactions fail to comply with governmental reporting requirements. Also called the underground, informal, or parallel economy, the shadow economy includes not only illegal activities but also unreported income from the production of legal goods and services, either from monetary or barter transactions. Hence, the shadow economy comprises all economic activities that would generally be taxable were they reported to the tax authorities. A precise definition of the shadow economy, however, is quite difficult because the shadow economy develops all the time, adjusting to changes in taxation and regulations. Shadow economy is a complex phenomenon that has become significant in Ukraine. This phenomenon in Ukraine is one of the main barriers to European integration, increasing competitiveness in the world market, improving living standards within the country. The presence of a shadow economy indicates the activity of illegal economic activity in the country, a high level of corruption in the public sector, a low level of legal and tax morality in society. Ukraine still has a significant volume shadow economy, which significantly impairs the socio-economic development of the state. Shadow economy has become one of the most acute economic and socio-political problems in Ukraine and poses a threat to the economic and national security of the state. The shadow economy is present unevenly in different sectors of the economy. Determining the level of the shadow economy allows the government to identify which sectors have to be given priority. The work based on the analysis of a significant array of analytical and statistical material. The problem of a significant level of shadowing of the economy in Ukraine is considered. The article describes the method of calculating the level of the shadow economy and compares the levels of the shadow economy in Ukraine from 2010 to 2020. Authors study the causes and consequences of shadowing a country's economy and describe possible ways to overcome the negative phenomenon.